Estudio de prefactibilidad para la implementación de un centro de formación para el alto rendimiento de jóvenes futbolistas - Quiñonez López, Juan Luis (2015)
The present project consisted in evaluate the feasibility to implement a centre of formation of young boys to become professional football players, with a target market consistent of boys that live in the city of Lima , between 12 and 18 years old , belongs to the socioeconomic level A,B,C ; that practices football and would like to become professional players. After evaluating the demand using geographic, demographic and psychographic criteria; it was estimated in 157,589 young boys that would like to acquire the services of the centre. Upon the result of this evaluation it was effectuated the analysis of the full project.